The Tibetan Medicinal Formula Ruyi Zhenbao: Research progress on pharmacological actions, clinical evidence and compatibility - Cairang Xiadao; Pengcuo Danzhi; Tsedien Nhamdriel; Dongzhi Yangchang; Chenlei Ganghuan; Yongzhong Zeweng; Zhang Wang; Ma Mi (Frontiers in Pharmacology, 2026)
Objective To comprehensively review the research progress on the compatibility principles, pharmacological mechanisms, and clinical evidence of the Tibetan medicinal formula Ruyi Zhenbao. Methods Guided by fundamental Tibetan medical theory, a critical review of domestic and international literature was conducted, systematically integrating Tibetan medicinal compatibility theory, preclinical pharmacological evidence, and clinical research data. Results Based on the multi-level medicinal property compatibility structure of Tibetan medicine, this formula combines 30 medicinal materials according to their properties and effects, forming a synergistic therapeutic system with heat-clearing, mind-awakening, collateral-dredging, and serous-fluid-drying properties. Preclinical studies indicate that Ruyi Zhenbao Formula may exert integrative regulatory effects through multiple targets and pathways, demonstrating multiple pharmacological activities including neuroprotection and repair, anti-inflammatory and immunomodulation, multi-mechanism synergistic analgesia, and microcirculation improvement. Clinical evidence suggests that this formula demonstrates potential efficacy in conditions such as osteoarthritis, cerebrovascular diseases, and neurological disorders, with acceptable safety profiles based on available data. Conclusion Current preclinical and clinical evidence supports the traditional applications of the Ruyi Zhenbao Formula and provides preliminary scientific insights into the Tibetan medical theories underlying its use. This review contributes to understanding the potential of integrating traditional Tibetan medical knowledge with modern biomedical research. However, a ConPhyMP-based quality assessment showed that none of the included primary studies reported voucher specimens or chemical fingerprints, underscoring the need for standardized phytochemical characterization in future research.